Pengaruh Review Online pada Online Travel Agent terhadap Minat Beli Kamar di Hotel SSU Bali - Pande Putu Dananjaya; I Nyoman Sukana Sabudi; Kadek Andita Dwi Pratiwi (BADAN PENERBIT STIEPARI PRESS, 2025)
The development of digital technology, particularly through the use of Online Travel Agent (OTA) platforms, has significantly changed consumer behavior in choosing hotels. One of the most notable changes is the use of online reviews as a form of electronic word of mouth (eWOM), which influences consumer perceptions and purchase decisions. Online reviews allow consumers to share experiences and rate the services provided by hotels, which can, in turn, influence the purchasing decisions of potential guests. This study aims to determine the effect of online reviews on OTA platforms on the purchase interest of rooms at Hotel SSU Bali. The research is quantitative with a descriptive approach, aiming to provide a clear picture of how online reviews affect purchasing decisions. A sample of 100 respondents was selected using purposive sampling. Data were collected through questionnaires and analyzed using simple linear regression, validity tests, reliability tests, normality tests, and t-tests. The results of the study show that online reviews have a positive and significant effect on purchase interest. The linear regression test showed a significance value of 0.000, which is less than 0.05, indicating a significant influence of online reviews on room purchase interest. Additionally, the coefficient of determination of 81.3% suggests that online reviews explain 81.3% of the variation in room purchase interest. Therefore, positive online reviews can increase the trust of potential guests and encourage them to make a purchase decision for rooms at Hotel SSU Bali. Overall, this study provides evidence that online reviews play a crucial role in consumer purchasing decisions and recommends that hotels enhance service quality and encourage guests to leave positive reviews to attract more potential customers.